PENGARUH CORPORATE SOCIAL RESPONSIBILITY, KINERJA LINGKUNGAN DAN GREEN PROCESS INNOVATION TERHADAP KINERJA KEUANGAN PERUSAHAAN: Studi Empiris pada Perusahaan Pertambangan yang terdaftar di Bursa Efek Indonesia Tahun 2019-2021 - Jenny Marcelina B; I Ketut Yudana Adi; Made Christin Dwitrayani (Universitas Triatma Mulya, 2023)
The company’s inancial performance is a description of teh condition andachievements o a company in its business activities. Currently, in carrying out itsbusiness, companies are required to be able to fulfill their responsibilities notonly to shareholders but also to stakeholders by presenting non-financialinformation in the form of economic, social and environmental performance.Therefore this study uses the variables corporate social responsibility,environmental performance and green process innovation as independentvariables and the company's financial performance as the dependent variable. Sothe purpose of this study is to determine the effect of corporate socialresponsibility (X1) on environmental performance (X2) and green processinnovation (X3) on company financial performance (Y) empirical studies onmining companies listed on the IDX in 2019-2021. The population in this studyamounted to 47 companies. The sample determination technique used purposivesampling to obtain a total of 54 samples. The data analysis technique used isdescriptive analysis, classical assumption test, multiple linear regressionanalysis, t-test analysis, F test and determination analysis. The results of theregression model analysis show Y = -1.165 + 0.432X1 + 0.115X2 + 1.301X3.The conclusion obtained is that corporate social responsibility does not affect thecompany's financial performance. Environmental performance has a positiveeffect on the company's financial performance. Green process innovation has apositive effect on the company's financial performance.